Temporal analysis of the occurrence of hot spots and land use and cover in the municipality of Marabá, Pará, Brazil (Research, Society and Development, 2022)
Anthropic interventions in the environment are constant and evolving processes. Since the dawn of humanity, man has changed the course and form of interaction with nature in the struggle for survival, and among the tools of intervention stand out, burning and deforestation. This study aims to analyze the dynamics of hotspots and land use and coverage referring to the years 2010, 2012, 2014, 2015, 2017 and 2019. This occurrence was classified into five classes: very low, low, medium, high, and very high. The vector data were obtained from the platforms of the Institute for Spatial Research - INPE and from the Mapbiomas project of collection 5. Qgis 3.10.12 Corunã was used for the elaboration of the maps. It was verified that the Very Low class remained constant during the studied period, the Medium, High and Very High classes were concentrated in the center and east of the municipality. The highest occurrence of hot spots occurred in the months of August to November, with a peak in October, in all years. Results of the analysis of land use and land cover between the years 2010 to 2019 are presented. It is observed that the occupied areas in 2010 grow constantly, in the anthropized area class in relation to the other classes water body and vegetation. The vegetation class presented a loss of 10,675,143.29 ha of area, which in the year 2010 evidences 32.41%, and in 2019 the percentage value of area was 30.07%, representing a total loss of 2.34%. The results demonstrated in this research assist in the prevention and combat of forest fires through spatial and temporal representation that is extremely useful in the planning of combating irregular burning in Marabá.